RETREAT: A REal-Time TREmor Analysis Tool for Seismic Arrays, With Applications for Volcano Monitoring - Smith, Patrick J.; Bean, Christopher J. (Frontiers in Earth Science, 2020)
Volcanic tremor is a sustained seismic signal associated with volcanic unrest and is often linked to movement of magmatic fluids in the subsurface. However, signals with similar spectral content can be generated by other surface processes. Hence, one of the best ways of distinguishing between different possible mechanisms is by tracking the location of its source, which is also important for mitigating volcanic risk. Due to its emergent nature, tremor cannot be located using travel-time based methods, therefore alternatives such as amplitude-based techniques or array analysis must be used. Dense, small-aperture arrays are particularly suited for analyzing volcanic tremor, yet costs associated with installation and maintenance have meant few long-term or permanent seismic arrays in use for routine monitoring. Given the potential for wider usage of arrays, this work presents a python-based software tool that uses array data and array processing techniques to analyze and locate volcanic tremor signals. RETREAT utilizes existing routines from the open-source ObsPy framework to carry out analysis of seismic array data in real-time and performs f-k (frequency-wavenumber) analysis, or Least-Squares beamforming, to calculate the backazimuth and slowness in overlapping time windows, which can help track the location of volcanic tremor sources. A graphical, or web-based, interface is used to configure a set of input parameters, before fetching chunks of waveform data and performing the array analysis. On each update the tool returns several plots, including timeseries of the backazimuth and slowness, a polar representation of the power and a map of the array with dominant backazimuth overlaid. The tool has been tested using real-time seismic data from the small-aperture SPITS array in Spitsbergen, as well as on data from an array deployed during the 2014 eruption of Bárðarbunga volcano, Iceland. Configuration files and waveform data for these examples are supplied with the distribution. RETREAT can also be used for infrasound and has been tested on infrasonic array data recorded at Mt. Etna, Italy. RETREAT is intended for use in real-time monitoring settings and it is hoped that it will facilitate greater use of arrays in tracking volcanic tremor sources in real-time, thereby enhancing monitoring capabilities.